Antimicrobial activity of biosynthesized silver nanoparticles using Diospyros celebica Bakh. (Eboni) extra. Issue 1 (February 2020) - Handayani, W; Zukhrufa, H; Yasman,; Imawan, C
Abstract: Silver nanoparticles (AgNPs) are known to exhibit an efficient, wide spectrum of antimicrobial properties. Certain metabolite compounds in plants can be used as reducing agents for silver ions reduction into AgNPs. The potential of Diospyros celebica extract was used to synthesize AgNPs and it was tested for their antibacterial activity. The phytochemical screening of the extract revealed the presence of phenols and saponins. For biosynthesis, 2% (w/v) of the extracts were treated with 0.01, 0.1, 1, and 10 mM of AgNO3 as precursors in a ratio of 1:9 (v/v). AgNP formation was confirmed by the observation of the solution color change from yellow to brown as well as by UV–Vis spectrophotometry, which revealed a peak at 350–500 nm. The nanoparticle size and shape confirmed using a Particle Size Analyzer (PSA) and Transmission Electron Microscope (TEM). The antibacterial activity of AgNPs against Escherichia coli and Staphylococcus aureus was examined by the well diffusion method. The results revealed that AgNPs synthesized by using the D. celebica extract exhibit antimicrobial activity for E. coli, which was indicated by the formation of clear zones. This result paves opportunities to develop an antimicrobial agent trough this method optimization.